The assessment of liquefied natural gas (LNG) demand reversibility in selected OECD countries - Vida Varahrami; Mohammad Saeed Haghighat (Energy Reports, 2018)
Experience has shown that there is a relationship between demand and price, contrary to the short-term mode, which is expected to be inverted between price and value, and the effects of lowering and rising prices follow reverse. But symmetric results; in the long run, there may be unlawful reactions It would seem that the effect of the price increase and its effect on the amount with its photo mode is not the effect of the price decline. To illustrate the effects of price symmetry, the price can be broken down into three parts, the maximum price, the lowering price, and the increasing price, according to the Getely method. The main objective of this paper is to investigate the effects of the LNG product in the OECD countries. The study uses seasonal data from 2011-2015 for selected countries (Japan, South Korea, United States, United Kingdom, and Spain). Dynamic panel method is also used to estimate the model of this research. According to research findings, long-term and short-term elasticities of effective factors on LNG demand in selected countries have been calculated. The results show that LNG demand in the selected importing countries is relatively reversible in the short and long-term.
Keywords: 330; Dynamic panel; Asymmetric effects; LNG; Reversibility